Common Mode Voltage Mitigation in Industrial Three-Phase Inverters Based on Model Predictive Control - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2018)
Common Mode Voltage (CMV) in variable speed drives is a source of electromagnetic interference and bearing currents. These issues are exacerbated in underground mining applications due to the specific earthing and protection requirements. This paper compares two inverter options for an industrial AC drive: a three-leg inverter and a four-leg inverter, with the view of CMV mitigation. The CMV mitigation strategy is based on Model Predictive Control (MPC). To reduce the computational burden associated with MPC, a computationally efficient modified model predictive control (MMPC) strategy is presented. The findings of the paper are validated by extensive simulations in the Matlab-Simulink c software environment. The presented results show a significant reduction of CMV in three-leg inverter and a complete CMV elimination in four-leg inverter. Experimental validation of the results presented in the paper is underway. © 2018 IEEE